GATA4 variant interaction with brain limbic structure and relapse risk: a voxel-based morphometry study - Zois, Evangelos; Vollstädt-Klein, Sabine; Kiefer, Falk (European neuropsychopharmacology, 2016)
Atrial natriuretic peptide (ANP) receptors are highly expressed in the amygdala, caudate and hypothalamus. GATA4 gene encodes a transcription factor of ANP associated with the pathophysiology of alcohol dependence. We have previously demonstrated that the GATA4 single nucleotide polymorphism (SNP) rs13273672 revealed stronger alcohol-specific amygdala activation associated with lowered relapse risk to heavy drinking at 90 days in the AA-homozygotes. Our understanding however with respect to GATA4 variation on gray matter (GM) regional amygdala, caudate and hypothalamus volume is limited. We investigated GM differences specific to GATA4 and hypothesized that GM alterations will be predictive of heavy relapse. Eighty-three recently detoxified alcohol dependent patients were included. Neuroimaging data was analyzed using Voxel Based Morphometry (VBM). The main effects of GM volume and genotype as well as their interaction effect on time to heavy relapse (60 and 90 days) were analyzed using cox regression. Significant higher GM volume was found for the AA-genotype group compared with AG/GG-genotype in the hypothalamus and caudate. A significant interaction was revealed between caudate and amygdala GM volume and GATA4 genotype on time to heavy relapse. The interaction was expressed by means of higher GM in the AA genotype group to be associated with reduced risk to relapse whereas in the AG/GG group higher GM was associated with increased risk to relapse. This is the first report on GM regional volume alterations specific to GATA4 genotype [(SNP) rs13273672] and its association with relapse in alcohol dependence. Current findings further support the role of GATA4 in alcoholism.
Gesehen am 21.01.2019
Available online 7 July 2016